FNIP1 Deficiency: Pathophysiology and Clinical Manifestations of a Rare Syndromic Primary Immunodeficiency - Samuele Roncareggi; Brian M. Iritani; Francesco Saettini (Current Issues in Molecular Biology)
Folliculin-interacting protein 1 (FNIP1) is a key regulator of cellular metabolism and immune homeostasis, integrating nutrient signaling with proteostasis. FNIP1 forms a complex with folliculin (FLCN) to regulate the mechanistic target of rapamycin complex 1 (mTORC1), functioning as a GTPase-activating protein (GAP) for RagC/D. Additionally, FNIP1 interacts with heat shock protein 90 (HSP90) and undergoes phosphorylation, glycosylation, and ubiquitination, which dynamically regulate its stability and function. Evidence from murine models suggests that FNIP1 loss disrupts immune cell development and mitochondrial homeostasis. However, FNIP1 deficiency in humans remains incompletely characterized, and its full phenotypic spectrum is likely underestimated. Notably, FNIP1-deficient patients exhibit immunological and hematological abnormalities, immune dysregulation, and metabolic perturbations, emphasizing its role in cellular adaptation to stress. Understanding the mechanistic basis of FNIP1 dysfunction in human tissues will be critical for delineating its contributions to immune and metabolic disorders and identifying targeted interventions.